Customers' satisfaction and loyalty for airlines e-ticketing and services in Malaysia - Nor Alina binti Ismail (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2018)
Internet technology provides vast opportunity to improve many e-services in various industries including the airline industry. Many companies nowadays are considering website as an important electronic platform for their business strategies in selling and advertising their products online. Based on current statistic, one of the highest electronic transactions in Malaysia for the past few years is flight e-tickets. Most major airline companies in Malaysia like MAS, AirAsia, and Malindo offer e-ticketing service as part of their business strategic initiatives to increase sales and improve customer service. This is provided as part of their e-CRM approach, which aims at improving customer satisfaction and eventually loyalty among customers. Despite an increase in flight e-tickets sales over the years, and each airline conducted its own customer satisfaction survey, not much is known about the overall level of customer satisfaction towards airline e-ticketing system in the country and the impact of e-ticketing on customer loyalty. The purpose of this study therefore is to fill these gaps. The study provides a conceptual framework upon which validation and assessment were done to measure the level of customer satisfaction for the airline industry. A field study has been employed to refine and validate the research model. Quantitative approach with questionnaire survey was used to collect data. In this research, 508 useful responses were used for the analyses by using the SPSS tool and Structured Equation Modelling technique. The finding indicates that e-CRM features at pre-purchase and post-purchase stages of online transaction have a significant effect on e-satisfaction among airline customers, which eventually lead to customer loyalty. Based on the result, it appears that web features such as promotion, post-booking and customer services, are important features that requires more attention by the airlines. While for offline services, the result shows that airport services and trust have the strongest impacts on the overall customer satisfaction. Thus, the study concluded that both the online and offline services are important determining factors in increasing the level of customer satisfaction towards airline services. Additionally, the study revealed that overall customer satisfaction positively influences customer loyalty towards the airlines. Customer loyalty involves developing long-term relationship with the airline company. This study contributes towards providing a model, based on Transaction Cycle, looking at factors that affect customer satisfaction and customer loyalty for airline e-ticketing system in Malaysia. Practically, the findings of this study offer insights to the airline management on key e-CRM features and services that the company should focus on to gain customer loyalty and improve competitiveness in a global environment.